Design of experiments (DoE) to develop and to optimize extraction of psychoactive substances. Issue 12 (10th March 2023) - Tang, Tiantian; Chen, Wanyi; Li, Lixian; Cao, Shurui
Abstract : The design of experiments (DoE) method was employed to optimize the adsorption processes of seven psychoactive substances in environmental water samples. The analytes were determined by UHPLC-MS/MS. Abstract : The design of experiments (DoE) method was employed to optimize the adsorption processes of seven psychoactive substances in magnetic solid phase extraction. Fe3 O4 /GO/ZIF-8 was utilized as an adsorbent for the efficient extraction of psychoactive substances from environmental water samples. The analytes were ephedrine, methylephedrine, amphetamine, methamphetamine, morphine, papaverine, and thebaine, which were determined by ultrahigh performance liquid chromatography-tandem mass spectrometry. Plackett–Burman design was employed to identify the significant factors responsible for adsorption, and Box–Behnken design was used for further optimization to obtain the optimum values for each variable. The predicted and experimental values were found to be in good agreement. The coefficient of determination ( R 2 ) values of 0.9500–0.9976 indicated that the model was significant. The linear ranges were 1–100 ng mL −1, and the correlation coefficient was good ( r 2 ≥ 0.995). The EF with values of about 2.5 was obtained with recoveries in the range of 74.92–94.47%. The limits of detection (LOD) and limits of quantification (LOQ) were 0.086–0.353 ng mL −1 and 0.286–1.175 ng mL −1, respectively. The intra-day and inter-day RSDs were in the range of 0.17–1.87% and 0.06–2.21%, respectively. By using the DoE method, the errors associated with inferring the influence and interaction between various factors can be reduced. The combination of MSPE and DoE improves the recovery, precision, and simultaneous detectability of the target analytes. It has a high potential for psychoactive substance analysis in environmental water.